MANAJEMEN RADIO LOKAL DALAM MEMPERTAHANKAN EKSISTENSI DI ERA DIGITAL: (Studi Kasus Manajemen Stasiun Radio di Bangka) - Rahmadini, Rahayu; Putri, Sekar; Arifah, Arifah; Kusuma, Rafles Abdi (MEDIOVA: Journal of Islamic Media Studies, 2024)
The development of communication technology in the digital era has reached the increasingly large capacity of society with its demands, especially in meeting information needs. Information can be an important commodity in people's lives. Technology that has developed over time has also shown the development of human civilization in each era, which means that human civilization today is more advanced than in ancient times. However, current developments and technological advances have not made radio dead in the ears of listeners. The aim is to find out how local radio management maintains its existence in the Digital Era. Research Methodology This is different from the qualitative research data collection method, namely case study data from interviews, observations and archives. As for this research, the case study was chosen based on the uniqueness of the incident where local radio in Bangka Belitung is an archipelagic area and has ethnic, tribal, cultural and religious diversity, as well as to obtain more complete information, so that the resulting understanding of the case studied is more complete. in depth so that media management is in accordance with the theories and principles of media management.